Nanomedicine and regulatory science: the challenges in Africa - Nyazema, N. Z.; Chanyandura, J. T.; Kumar, P. O. (Frontiers in Biomaterials Science, 2023)
The integrated approach in the development of nanotechnology is allowing its introduction into multiple fields, including pharmaceutical research, in which there are now several medicines containing nanomaterials or at least making nano-based claims. As a result of increasing research in nanotechnology, pre-existing medicines have been reformulated, and new medicines have been developed. This has brought challenges to the current regulatory frameworks in Europe and the United States. These regulatory agencies are known to be stringent because they have both the human capacity and skills and conducive policies and the landscape to manage new technology, unlike the agencies in most African countries. Because the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) have embraced regulatory science (RS) as a means of proactive analysis of regulatory principles, those agencies will be able to address nanomedicine challenges in a straightforward manner. African countries currently do not have a harmonized regulatory framework because different national regulatory authorities are at different levels of development. The pharmaceutical sector in Africa is facing many challenges, including the non-existence of research and development partnerships between industry, universities, and research institutions that foster nanomedicine development. Now that the African Medicine Agency (AMA) is in place, Africa should see the rapid implementation of the AU Model Law on Medical Products Regulation that will assist in putting in place capacity-building programs in nanomedicine RS.